ANALISIS PENGARUH STRUKTUR KEPEMILIKAN TERKONSENTRASI, KOMPLEKSITAS, PROFITABILITAS, DAN RISIKO PERUSAHAAN TERHADAP AUDIT FEE - Aulia Dewi Afdhalastin; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2021)
The different business environment in each company causes the audit fees used by each company to be different for external auditors. This study aims to examine the effect of family ownership, government ownership, institutional ownership, complexity, profitability and client risk as independent variables on audit fees as the dependent variable.The sample data population in this study were all LQ45 companies listed on the IDX in 2015 - 2019. The purposive sampling method was used in this study to determine the sample company data to be tested. Using this method, data were obtained for 106 companies from the total data of 350 companies.The results of this study indicate that the variables of family ownership and institutional ownership have a positive and significant relationship with the audit fee. The independent variables of client complexity, client profitability and client risk have a negative and significant relationship with the dependent variable on audit fees. Meanwhile, the goverment ownership has a significant positive relationship to the audit fee.